Pendidikan Kesehatan tentang Bullying di SMPN 5 Lebak Bandung Kota Jambi - Fajri, Jufri Al; Suri, Marta; Putri, Vevi Suryenti; Maidaliza, Maidaliza (Jurnal Abdimas Kesehatan (JAK), 2025)
Bullying is one of the most common psychosocial problems among adolescents, particularly within the school environment. A lack of knowledge and awareness among students regarding the forms and impacts of bullying can increase the risk of deviant behavior and mental health problems, ultimately affecting academic performance. This community service activity aimed to enhance students’ knowledge about bullying through health education using visual media (PowerPoint). The activity was conducted face-to-face on January 15, 2023, with 27 students from class VIII J of SMP Negeri 5 Kota Jambi participating. The implementation stages included preparation, pre-test, delivery of educational material, interactive discussion, post-test, and evaluation. The results showed a significant improvement in students’ knowledge: before the intervention, 62.9% of students had poor knowledge, while after the intervention, 88.8% demonstrated good knowledge. These findings indicate that health education using visual media is effective in improving students’ understanding of bullying. It is expected that this program will contribute to creating a safe, inclusive, and violence-free school environment.